Spontaneous orbitofacial neurofibroma in a sow - Joanna Vargas Zillig Echenique; Fernanda Felicetti Perosa; Giuliano Orlandi Suzin; Manoela Marchezan Piva; Rafael Biondo Rosa; Marcele Bettim Bandinelli; Saulo Petinatti Pavarini (Ciência Rural, 2023)
ABSTRACT: Neurofibromas are neoplasms derived from nerve bundles and are frequent in humans but not common in animals. This report described the macroscopic, histologic, and immunohistochemistry findings of an orbitofacial neurofibroma in a sow. The sow presented left eyelids with marked expansion, associated with severe ectropion and reddening of both conjunctival mucosae. The mass on the cutting surface was homogeneous, with a light tan, and shiny, measuring 9.0 x 7.0 x 7.0 cm in width, compressing the eyeball. Microscopically, there was paucicellular neoplastic proliferation of elongated cells amid the accentuated myxoid matrix. There were multifocal areas where well-differentiated nervous fascicles and skeletal musculature were seen. Neoplastic cells were immunostained positive for GFAP, neurofilament, S-100, Sox-10, and vimentin. Cytokeratin showed immunolabeling around primitive nerve bundles and desmin around neoformed vessels and muscle bundles within the tumor. Orbitopalpebral and orbitofacial neurofibroma, despite being common in humans, have not been described in domestic pigs and should be considered as a differential diagnosis in eyelid tumors in pigs.